Theoretical study on the spectroscopic properties of the low-lying electronic states and the laser cooling feasibility of the CaI molecule. (August 2021) - Li, Dong-Ying; Yang, Chuan-Lu; Sun, Zhao-Peng; Wang, Mei-Shan; Ma, Xiao-Guang
Highlights: The potential energy curves of the four electronic states of CaI are obtained. The spectroscopic parameters, the vibrational energy levels are determined. The optical laser cooling schemes are suggested for CaI. Cooling effect is evaluated with scattering photon number and Doppler temperature. The modified AP function is proposed to fit the transition dipole moments. Abstract: The potential energy curves (PECs) and transition dipole moments of four electronic states of the CaI molecule are obtained by the multireference configuration interaction method and the atomic natural orbital-relativistic core-correlated basis sets. Davidson correction, relativistic effect, and spin–orbit coupling splitting are also included. The rotational and vibrational energy levels of each electronic state are determined by solving the Schrödinger equation of nuclear motion using the obtained PECs. The spectroscopic parameters are fitted from the obtained energy levels by using the Dunham expression. The Franck–Condon factors, radiative lifetimes, and radiative widths between the ground electronic state X 2 Σ + and A 2 Π1/2 / 2 Π3/2 /B 2 Σ + states are calculated. Finally, the optical scheme for laser cooling is proposed based on the obtained spectroscopic properties. Results demonstrate that the CaI molecule could be a promising candidate for laser cooling. Graphical abstract: Image, graphical abstract